Evaluating fabric-based IMU and blue trident system against optical motion capture for lower body kinematics in badminton specific movement - Tan, K.; McErlain-Naylor, S. A. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: In the biomechanical analysis of badminton, a sport necessitating high precision and agility (1), optical motion capture is the established standard despite its high cost and operational limitations in natural settings (2). Recent advancements in wearable technology, particularly fabric-based and Blue Trident IMU systems, have emerged as viable alternatives, reputed for their ease of use and adaptability to various environments (3). This study critically evaluates these novel IMU technologies in comparison with traditional optical systems, focusing on their capability to accurately record lower body joint kinematics during dynamic badminton movements. The findings are intended to guide future research and enhance biomechanical applications in sports, potentially influencing training, performance analysis, and injury prevention. METHODS: Ten university-level badminton players volunteered. Demographic and anthropometric data, including age, gender, height, weight, and limb measurements were recorded, to inform biomechanical analyses. Participants were equipped with fabric-based IMU leggings and the Blue Trident system to evaluate their efficacy in capturing lower body joints kinematics during specific badminton actions: front forehand lunges, front backhand lunges, and jumping smashes. Each action was performed in three sets of three repetitions, under shuttlecock feeds to mimic game conditions, ensuring the ecological validity of the data collected. Data were analyzed to compare the accuracy and consistency of the IMU systems against traditional motion capture benchmarks, focusing on key lower body kinematic variables. The study adheres to ethical guidelines, with procedures designed to minimize risk and ensure participant safety, concluding with a standard cooldown protocols. RESULTS: The studys comparative analysis of the Blue Trident IMUs and fabric-based IMU against conventional optical motion capture systems demonstrated adequate concurrent validity during low-velocity badminton maneuvers. Nevertheless, the precision of IMU devices attenuated with the escalation of movement speed. Notably, during expedited lunges aimed at shuttlecock interception, both IMU modalities recorded deviations from the mocap data, indicating a potential limitation in their capacity to track rapid biomechanical events with high fidelity. CONCLUSION: The study indicates that while IMU systems, including fabric-based and individuals IMU unit, show promise for biomechanical analysis in badminton, their accuracy diminishes with increased movement speed. This suggests potential for IMUs in practice settings but also highlights the need for enhanced sensitivity in high-velocity scenarios. Further research should focus on improving IMU precision for rapid sports movements to fully harness their practicality in real-world applications.